Analisis Penerapan Metode Activity Based Costing Method Untuk Meningkatkan Akurasi Dalam Menentukan Perhitungan Harga Pokok Produksi - Bondan Wirajaya; Hanif Ismail (AKUNTANSI 45, 2024)
The aim of this research is to determine the application of the Activity Based Costing method to increase the accuracy of production cost calculations. The research method used in this research is a descriptive research method using a case study approach which took the research location in Puspita, Jakarta City. The results of this research show that the calculation of production costs using the traditional analytical accounting method is IDR 15,978.15 while the Activity Based method of determining the cost of production Costing is IDR 15,766.36 so there is a price difference in the D lunch box production method at Pupita Catering Town Jakarta, which is more appropriately applied to operating costs based on the difference of IDR. 211.79 is lower compared to traditional cost accounting methods because factory overhead costs are allocated to several cost drivers so that operating costs can be allocated to products correctly and precisely according to the consumption of each activity.